Black Gotham : a family history of African Americans in nineteenth-century New York City - Peterson, Carla L., 1944- (Yale University Press, 2011)
Narrates the story of the elite African American families who lived in New York City in the nineteenth century, describing their successes as businesspeople and professionals and the contributions they made to the culture of that time period.